Thermal stability of methyltrimethyltridecylchromans (MTTCs) in reservoired oils in the Miaoxi area, Bohai Bay Basin, East China - Xiaoyong Yang; Youjun Tang; Peng Sun; Yiming Hu; Haifeng Yang; Feilong Wang (Journal of Asian Earth Sciences, 2026)

Sustainable treatment and valorization of MSWIFA for construction materials: Technologies, mechanisms, and challenges - Zhiyuan Han; Guangcheng Long; Fan Wang; Kunlin Ma; Zhuo Tang; Youjun Xie; Ming Chen; Ding Jiang; Wenxiang Xie; Yan Liu (Journal of Environmental Chemical Engineering, 2026)

Evaluation of deconvolution methods and loading parameters in nanoindentation characterization of sodium aluminosilicate hydrate gel in fly ash based geopolymers - Wenrui Xu; Youjun Xie; Fan Wang; Zhiyu Luo; Gang Ma; Yiran Li; Yingjie Li; Guangcheng Long; Zhuo Tang (Journal of Cleaner Production, 2026)

Western Pacific subtropical high regulated the spatiotemporal pattern of East Asian summer monsoon precipitation during the Holocene - Linkai Wang; Junhuai Yang; Fuyuan Gao; Haoyu Wang; Canyi Zhang; Wenxi Qu; Jianye Li; Jinmeng Tang; Xin Liu; Yan Liu; Lai Zhao; Shuyuan Wang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Aryl isoprenoids in severe biodegradation oils from the Miaoxi Depression, Bohai Bay Basin - Xiaoyong Yang; Youjun Tang; Peng Sun; Yiming Hu; Haifeng Yang; Feilong Wang (Organic Geochemistry, 2025)

Methyltrimethyltridecylchromans (MTTCs) in Mature Crude Oils: Implications for Oil Family Classification and Palaeoenvironmental Diagnosis - Youjun Tang; Mengyue Han; Xiaoyong Yang; Ke Liu; Lian Chen; Yahao Mei; Yulu Han; Tianwu Xu; Chengfu Zhang (Journal of Marine Science and Engineering, 2025)
Methyltrimethyltridecylchromans (MTTCs), a class of oxygen-containing aromatic derivatives, have been used as indicators of paleosalinity in source rocks and crude oils. However, the reliability of these compounds as indicators in mature organic matter remains unclear, hindering a definitive assessment of their significance for oil–oil or oil–source rock correlation. In this study, a suite of mature oils and associated source rocks from the Paleogene Shahejie (E2s) Formation in the Machang area, Dongpu Depression, Bohai Bay Basin, were analyzed. The distribution of bulk compositions and biomarkers in the oils and source rock extracts suggests a genetic relationship, indicating that the oils were derived from similar organic matter (predominantly algae and aquatic macrophytes) and depositional environments (low salinity), with comparable maturity levels (within the middle oil window). The β/γ-MTTC ratio, a proposed maturity indicator, appears unreliable in mature organic matter, as evidenced by its poor correlation with established maturity proxies (e.g., C29 24-ethylcholestanes αββ/(ααα + αββ)) in the studied samples. In contrast, MTTC-based salinity paraments (α/δ, α/γ, MTTCI, and the cross-plot of MTTCI versus Pr/Ph) consistently reflect a low-salinity depositional environment for these crude oils and source rocks, except in the ternary diagram of relative alkylation abundances. These findings suggest that MTTC-derived paleosalinity indicators may serve as effective tools for oil–oil or oil–source rock correlation within the middle oil window. This study provides evidence supporting the broader applicability of MTTC-based proxies for paleosalinity reconstruction and correlation studies, particularly in mature organic matter under geological conditions. The results also offer insights for regional petroleum exploration in saline lacustrine basins.

Organic-inorganic geochemistry and paleontology reveal the Paleocene paleoecology and source rock development in the Lishui-Jiaojiang Sag, East China Sea Shelf Basin - Jiahao He; Dujie Hou; Youjun Tang; Ting Wang; Jun Qin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Identification and analysis of JHBP/TO family genes and their roles in the reproductive fitness cost of resistance in Frankliniella occidentalis (Pergande) - Kanghua Qian; Yanran Wan; Jiangjiang Yuan; Yingxi Tang; Xiaobin Zheng; Jing Wang; Hongyi Cao; Ying Zhang; Sirui Chen; Youjun Zhang; Qingjun Wu (Pesticide Biochemistry and Physiology, 2024)

Geochemical fingerprints of Dongpu Depression crude oils in Bohai Bay Basin, northern China: Insights from biomarkers and isotopic compositions of selected alkylnaphthalenes and alkylphenanthrenes - N’Guessan Francois De Sales Konan; Meijun Li; Youjun Tang; Erfan Mohammadian; Bo Liu; Andre Hyacinth Latyr Tine; Lukman Adesina Olayinka; Zhejun Pan (Organic Geochemistry, 2024)

Defect detection within filling layer of subway slab ballastless track based on impulse response method - Jiebo Peng; Xiaohui Zeng; Zhuo Tang; Guangcheng Long; Youjun Xie (Engineering Structures, 2024)

Uridine diphosphate glucosyltransferases are involved in spinosad resistance in western flower thrips Frankliniella occidentalis (Pergande) - Jing Wang; Yanran Wan; Ying Zhang; Jiangjiang Yuan; Xiaobin Zheng; Hongyi Cao; Kanghua Qian; Jiuming Feng; Yingxi Tang; Sirui Chen; Youjun Zhang; Xuguo Zhou; et al. (Journal of Hazardous Materials, 2024)

Impact of biodegradation on methyltrimethyltridecylchromans (MTTCs) in crude oils from the Bohai Bay Basin, China - Xiaoyong Yang; Youjun Tang; Yi Yang; Haifeng Yang; Feilong Wang; Xiaoxia Lü (Organic Geochemistry, 2023)

Palaeo-environmental significance of fibrous carbonate cement in Marinoan cap carbonates - Yongjie Hu; Chunfang Cai; Peng Sun; Hong Zhang; Zixuan Liu; Ying Li; Qiang Wang; Youjun Tang; Adrian Immenhauser (Marine and Petroleum Geology, 2023)

Curcumin-activated Olfactory Ensheathing Cells Improve Functional Recovery After Spinal Cord Injury by Modulating Microglia Polarization Through APOE/TREM2/NF-κB Signaling Pathway - Chao Jiang; Zhe Chen; Xiaohui Wang; Yongyuan Zhang; Xinyu Guo; Hong Fan; Dageng Huang; Yuqing He; Xiangwen Tang; Yixiang Ai; Youjun Liu; Hao Yang; et al. (Journal of Neuroimmune Pharmacology, 2023)
Transplantation of curcumin-activated olfactory ensheathing cells (aOECs) improved functional recovery in spinal cord injury (SCI) rats. Nevertheless, little is known considering the underlying mechanisms. At the present study, we investigated the promotion of regeneration and functional recovery after transplantation of aOECs into rats with SCI and the possible underlying molecular mechanisms. Primary OECs were prepared from the olfactory bulb of rats, followed by treatment with 1µM CCM at 7–10 days of culture, resulting in cell activation. Concomitantly, rat SCI model was developed to evaluate the effects of transplantation of aOECs in vivo. Subsequently, microglia were isolated, stimulated with 100 ng/mL lipopolysaccharide (LPS) for 24 h to polarize to M1 phenotype and treated by aOECs conditional medium (aOECs-CM) and OECs conditional medium (OECs-CM), respectively. Changes in the expression of pro-inflammatory and anti-inflammatory phenotypic markers expression were detected using western blotting and immunofluorescence staining, respectively. Finally, a series of molecular biological experiments including knock-down of triggering receptor expressed on myeloid cells 2 (TREM2) and analysis of the level of apolipoprotein E (APOE) expression were performed to investigate the underlying mechanism of involvement of CCM-activated OECs in modulating microglia polarization, leading to neural regeneration and function recovery. CCM-activated OECs effectively attenuated deleterious inflammation by regulating microglia polarization from the pro-inflammatory (M1) to anti-inflammatory (M2) phenotype in SCI rats and facilitated functional recovery after SCI. In addition, microglial polarization to M2 elicited by aOECs-CM in LPS-induced microglia was effectively reversed when TREM2 expression was downregulated. More importantly, the in vitro findings indicated that aOECs-CM potentiating LPS-induced microglial polarization to M2 was partially mediated by the TREM2/nuclear factor kappa beta (NF-κB) signaling pathway. Besides, the expression of APOE significantly increased in CCM-treated OECs. CCM-activated OECs could alleviate inflammation after SCI by switching microglial polarization from M1 to M2, which was likely mediated by the APOE/TREM2/NF-κB pathway, and thus ameliorated neurological function. Therefore, the present finding is of paramount significance to enrich the understanding of underlying molecular mechanism of aOECs-based therapy and provide a novel therapeutic approach for treatment of SCI.

Seed priming with rutin enhances tomato resistance against the whitefly Bemisia tabaci - Juan Tang; Haowei Shen; Rong Zhang; Fengbo Yang; Jinyu Hu; Jinting Che; Hongyan Dai; Hong Tong; Qingjun Wu; Youjun Zhang; Qi Su (Pesticide Biochemistry and Physiology, 2023)

Identification, distribution and geochemical significance of benzo[b]naphthofurans and benzo[b]naphthothiophenes in source rocks from the Beibuwan Basin, South China Sea - Xin Wang; Meijun Li; Taotao Yang; Bang Zeng; Yang Shi; Xiaoqiang Liu; Youjun Tang (Chemical Geology, 2023)

Simple column chromatography separation procedure for polycyclic aromatic hydrocarbons: controlling factor(s) - N’Guessan Francois De Sales Konan; Meijun Li; Shengbao Shi; Xue Liu; Youjun Tang; Amoako Kojo; Abdulkareem Toyin (Arabian Journal of Geosciences, 2022)

Effects of magnetically treated Sedum alfredii seeds on the dissolved organic matter characteristics of Cd-contaminated soil during phytoextraction - Youjun Tang; Shuaizhi Ji; Dan Chen; Jiawei Wang; Min Cao; Jie Luo (Environmental Science and Pollution Research, 2022)

The poultry pathogen Riemerella anatipestifer appears as a reservoir for Tet(X) tigecycline resistance - Zeeshan Umar; Qiwei Chen; Biao Tang; Yongchang Xu; Jinzi Wang; Huimin Zhang; Kai Ji; Xu Jia; Youjun Feng (Environmental Microbiology, 2021)
Summary The transferability of bacterial resistance to tigecycline, the ‘last‐resort’ antibiotic, is an emerging challenge of global health concern. The plasmid‐borne tet (X) that encodes a flavin‐dependent monooxygenase represents a new mechanism for tigecycline resistance. Natural source for an ongoing family of Tet(X) resistance determinants is poorly understood. Here, we report the discovery of 26 new variants [ tet (X18) to tet (X44)] from the poultry pathogen Riemerella anatipestifer , which expands extensively the current Tet(X) family. R. anatipestifer appears as a natural reservoir for tet (X), of which the chromosome harbours varied copies of tet (X) progenitors. Despite that an inactive ancestor rarely occurs, the action and mechanism of Tet(X2/4)‐P, a putative Tet(X) progenitor, was comprehensively characterized, giving an intermediate level of tigecycline resistance. The potential pattern of Tet(X) dissemination from ducks to other animals and humans was raised, in the viewpoint of ecological niches. Therefore, this finding defines a large pool of natural sources for Tet(X) tigecycline resistance, heightening the need of efficient approaches to manage the inter‐species transmission of tet (X) resistance determinants.

Origin and accumulation of natural gas in the Ningbo Tectonic Zone in the Xihu Sag - Daxiang He; Youjun Tang; Rongfu Shi (Arabian Journal of Geosciences, 2021)

An analysis of potential investment returns of planted forests in South China - Pu Zhang; Youjun He; Yiming Feng; Rafael De La Torre; Hongyan Jia; Jixin Tang; Frederick Cubbage (New Forests, 2019)

Inactivation of Dipeptidyl Peptidase IV Attenuates the Virulence of Streptococcus suis Serotype 2 that Causes Streptococcal Toxic Shock Syndrome - Junchao Ge; Youjun Feng; Hongfeng Ji; Huimin Zhang; Feng Zheng; Changjun Wang; Zhimin Yin; Xiuzhen Pan; Jiaqi Tang (Current Microbiology, 2009)

The involvement of sortase A in high virulence of STSS-causing Streptococcus suis serotype 2 - Changjun Wang; Ming Li; Youjun Feng; Feng Zheng; Yaqing Dong; Xiuzhen Pan; Gong Cheng; Ruiping Dong; Dan Hu; Xiaodan Feng; Junchao Ge; Di Liu; et al. (Archives of Microbiology, 2009)